Literature Study: Understanding Financial Literacy In University Student’s Consumptive Behavior - Rachmawati, Rizki Amalia (Jurnal Scientia, 2024)
Financial literacy is the knowledge, understanding, skills, and beliefs of humans who are able to manage finances well, optimally, and wisely. With this understanding of financial literacy, it is hoped that students will be able to consume something that is a need, not a desire, or consume wisely. This research method uses literature studies by searching from various sources such as books, articles that have related discussions. This study found that understanding financial literacy can be a good and wise decision-making in student consumer behavior. This economic literacy affects consumer behavior experienced by students. Therefore, good knowledge and understanding of financial literature are needed, so that students become wiser and more rational in consuming.